RADIOCARBON INVESTIGATION OF TWO LARGE AFRICAN BAOBABS FROM KIZIMKAZI, ZANZIBAR, TANZANIA - PATRUT, Adrian; PATRUT, Roxana T.; RAKOSY, Laszlo; RATIU, Ileana-Andreea; BODIS, Jenö; NASSOR, Nassor Mahmoud; VON REDEN, Karl F. (Studia Universitatis Babeș-Bolyai Chemia, 2022)
The article reports the AMS (accelerator mass spectrometry) radiocarbon dating results of Kizimkazi Big tree and Kizimkazi II baobab, two large African baobabs from Zanzibar, Tanzania. Unfortunately, both baobabs toppled and died in 2018 and 2020, during violent storms. The investigation of the two baobabs evinced that the first of them, which was also the biggest tree of Tanzania, consisted of 5 stems, out of which 2 were false ones, and had a closed ring-shaped structure. The second baobab was composed of 4 fused stems and had a cluster structure. Several wood samples were collected from the two baobabs. Seven segments were extracted from the samples and dated by radiocarbon. The oldest segment from Kizimkazi Big tree had a radiocarbon date of 312 ± 18 BP, corresponding to a calibrated age of 380 ± 10 calendar years. According to dating results, the Kizimkazi Big tree died at the age of 400 ± 25 years. The oldest segment from Kizimkazi II baobab had a radiocarbon date of 137 ± 17 BP, corresponding to a calibrated age of 190 ± 10 calendar years. This value indicates that the Kizimkazi II baobab was 250 ± 25 years old when it died.